ELTV Week-in-Review (African Knowledges and the History Publication since the 1970s, 1989)
News from different counties in Liberia; changes in license plates; corruption scandals in the ministry; advertisements from the Liberia Telecommunications Corporation; President's party (NDPL) and discussions on its relations with other parties; Liberia's relations with West Germany.
Keywords: News; Public Affairs